2009
DOI: 10.1242/jcs.045542
|View full text |Cite
|
Sign up to set email alerts
|

Dual modes of rabies P-protein association with microtubules: a novel strategy to suppress the antiviral response

Abstract: Conventional nuclear import is independent of the cytoskeleton, but recent data have shown that the import of specific proteins can be either facilitated or inhibited by microtubules (MTs). Nuclear import of the P-protein from rabies virus involves a MT-facilitated mechanism, but here, we show that P-protein is unique in that it also undergoes MT-inhibited import, with the mode of MT-interaction being regulated by the oligomeric state of the P-protein. This is the first demonstration that a protein can utilise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 48 publications
9
108
0
Order By: Relevance
“…In fact, by using a recombinant protein expression system, it was previously demonstrated that P3 inhibits nuclear translocation and DNA binding of STATs (11,17). Further, Marschalek et al (18) showed by using an RABV strain genetically modified to overexpress P2 that this isoform plays an important role in the IFN resistance of the virus.…”
mentioning
confidence: 99%
“…In fact, by using a recombinant protein expression system, it was previously demonstrated that P3 inhibits nuclear translocation and DNA binding of STATs (11,17). Further, Marschalek et al (18) showed by using an RABV strain genetically modified to overexpress P2 that this isoform plays an important role in the IFN resistance of the virus.…”
mentioning
confidence: 99%
“…Importantly, the results explain for the first time how, through dynamic interactions with MTs, MTAS-dependent MT interaction can facilitate nuclear import rather than resulting in cytoplasmic sequestration and consequently inhibition of nuclear import (47)(48)(49).…”
mentioning
confidence: 82%
“…This unique mechanism of rabies viral subversion of IFN signaling is critical to its pathogenicity, and also suggests novel targets for the development of antiviral drugs or attenuated viruses for vaccine applications [74].…”
Section: Viral Spread To the Cnsmentioning
confidence: 98%